Sweating rate and dehydration levels in professional soccer players after an official league match (Spanish Second Division B) - Gomez Vera, G.; Del Valle Pascual, F. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
One of the main reasons of performance loss is the dehydration caused by inadequate liquid intake during physical exercise. When 2% total body weight is lost due to the fluid loss, this compromises many physiological and cognitive functions, resulting in a decrease in performance. In soccer, to determinate hydration strategies it is very important to maintain the proper water balance and avoid a performance fall. Our aim was to describe the sweating rate and the dehydration levels in professional soccer players after an official league match of the Spanish Second Division B. Thirteen professional soccer players (20±2 years old, body weight 72±8 kg, height 175±5 cm) were analyzed before and after the match. The goalkeeper was excluded. The temperature during the match was 31±1ºC and relative humidity 61±4%. To assess weight loss, players were weighed nude before and after the match. The fluid intake calculation was determined by the difference in volume of the bottles from the start to the final of the game (2 bottles per player, one with 500 ml of mineral water, and another with 500 ml of a liquid with a 20% carbohydrate and 0.6% sodium). The measurement was done with a measuring cylinder. No player urinated during the game. Sweating rate was calculated as: Sweating rate = (weight loss + liquid intake - urine excreted)/ minutes of activity. We registered an activity time of 85±33 minutes. Weight loss was 929±473 g (range 0 - 1800 g), equal 1.3±0.6% (range 0.0-2.3%) of body mass. The liquid intake was 678±395 ml (range 290 - 1620 ml), and the sweating rate was 20±10 ml/min-1 (range 0-37 ml/min-1). The liquid intake from the studied sample was not enough for remedying the liquid loss caused by the dehydration. Therefore, it would be necessary to incorporate new hydration strategies that aim to achieve and maintain a proper water balance.